Securing Property Rights - Behrer, A. Patrick; Glaeser, Edward L.; Ponzetto, Giacomo A. M.; Shleifer, Andrei (Journal of Political Economy, 2021)
A central challenge in securing property rights is the subversion of justice. We present a model of a polluter whose discharges harm multiple owners, and we compare property rules, liability rules, and regulation on efficiency grounds. We provide conditions under which property rules are preferred to liability rules, thus verifying the Calabresi-Melamed conjecture. Regulation that enforces partial abatement may be preferred to either of the extreme rules. An empirical analysis of water quality in the United States before and after the Clean Water Act shows that the effects of regulation are consistent with several predictions of the model.